Teacher Human Resource Management in Strengthening Literacy and Numeracy in Elementary Schools - Ngatemiyati, Ngatemiyati; Kusumaningsih, Widya; Nuroso, Harto (Jurnal Ragam Pengabdian, 2026)
Teacher human resource management plays a vital role in improving the quality of literacy and numeracy learning in elementary schools by strengthening teachers' professional competencies and instructional practices. This study aimed to analyze the implementation of teacher human resource management in strengthening literacy and numeracy at SD Negeri Ngempon 02 Bergas, Semarang Regency, using the Planning, Organizing, Actuating, and Controlling (POAC) framework. A qualitative case study approach was employed. Data were collected through in-depth interviews, participant observation, and document analysis involving the principal, teachers, education staff, and school committee members selected purposively. Data credibility was ensured through source and technique triangulation, while analysis followed the interactive model of Miles, Huberman, and Saldaña. The findings reveal that teacher human resource management was implemented systematically through comprehensive planning, collaborative task organization, instructional leadership promoting teacher innovation, and continuous supervision through academic monitoring, evaluation, and follow-up. These integrated practices enhanced teachers' capacity to deliver literacy- and numeracy-oriented instruction while fostering a collaborative school culture that supports continuous professional development. The study concludes that strengthening literacy and numeracy depends not only on teachers' competencies but also on effective teacher human resource management supported by instructional leadership and sustainable quality improvement.